Σάββατο, 3 Σεπτεμβρίου 2016

$\dfrac{113A}{61}=?$

Αν 
$A = \dfrac{(4\cdot2^4 + 1)(4\cdot4^4 + 1)(4\cdot6^4 + 1)}{(4\cdot1^4 + 1)(4\cdot3^4 + 1)(4\cdot7^4 + 1)}$
τότε
$\dfrac{113A}{61}=?$

 Διασκεδαστικά Μαθηματικά    www.eisatopon.blogspot.com     

1 σχόλιο:

  1. $A=\dfrac{(4⋅2^4+1)(4⋅4^4+1)(4⋅6^4+1)}{(4⋅1^4+1)(4⋅3^4+1)(4⋅7^4+1)}=$
    $=\dfrac{(4⋅4^2+1)(4⋅16^2+1)(4⋅36^2+1)}{(4⋅1^2+1)(4⋅9^2+1)(4⋅49^2+1)}=$
    $=\dfrac{(8^2+1)(32^2+1)(72^2+1)}{(2^2+1)(18^2+1)(98^2+1)}$

    Όμως $p^2+1^2=p^2+1^2+2p-2p=$ $(p+1)^2-2p=$ $(p+1+\sqrt{2p})(p+1-\sqrt{2p})$

    οπότε:
    $8^2+1=(8+1+4)(8+1-4)=13\cdot 5$
    $32^2+1=(32+1+8)(32+1-8)=41\cdot 25$
    $72^2+1=(72+1+12)(72+1-12)=85\cdot 61$
    $2^2+1=(2+1+2)(2+1-2)=5\cdot 1$
    $18^2+1=(18+1+6)(18+1-6)=25\cdot 13$
    $98^2+1=(98+1+14)(98+1-14)= 113\cdot 85$

    και άρα :
    $\dfrac{113}{61}\cdot \dfrac{(13\cdot 5)(41\cdot 25)(85\cdot 61)}{(5\cdot 1)(25\cdot 13)(113\cdot 85)}=41$

    ΑπάντησηΔιαγραφή